Metrics, models and foresight for European sustainable food and nutrition security: The vision of the SUSFANS project. (June 2018) - Rutten, Martine; Achterbosch, Thom J.; de Boer, Imke J.M.; Cuaresma, Jesus Crespo; Geleijnse, Johanna M.; Havlík, Petr; Heckelei, Thomas; Ingram, John; Leip, Adrian; Marette, Stéphan; van Meijl, Hans; Soler, Louis-Georges; et al.
Abstract: This paper defines the research agenda of the SUSFANS project, describes its history and its potential societal impacts. It contributes to balanced and encompassing views on how to strengthen food and nutrition security outcomes in the EU and how to improve the performance of the food system in the EU from the perspective of social, environmental and economic sustainability. The research is led by the notion that improvements in the diets of the European consumer must come from, and be supportive of, sustainable food systems. Its holistic, integrative approach builds a set of metrics, models and foresight tools, useable for navigation on sustainable food and nutrition security. This results in a coherent and supported vision on sustainable food and nutrition security in the EU and globally, and underpins a perspective on how EU policies on farming, fishing, food and nutrition could contribute to that vision with greater efficacy than today. Graphical abstract: Image 3 Highlight: The SUSFANS project's research agenda, history and potential impacts are presented. It focuses on food and nutrition security and sustainable food systems in the EU. The leading notion is that both concepts come together in consumer diets. The project builds metrics, models and foresight tools useable in policy support. Its holistic and integrative approach results in a coherent and supported vision.